Kajian Tracer Study LulusanJurusan PTBB FT UNY Tahun 2012 - Noor Fitrihana; Prihastuti Ekawatiningsih; Ichda Chayati; Kapti Asiatun; Asi Tritanti (Jurnal Pendidikan Teknologi dan Kejuruan, 2014)
The objectives of this study were: (1) to describe the graduates’ profile of the Department of Fashion Design and Hospitality Education of 2010-2012 that is required by the National Accreditation Commision for Higher Education, (2) to examine the gap between the graduates’ competencies with the market needs. This tracer study is a descriptive survey study conducted from June to November 2012. The population were 241 graduates of the academic year of 2012. 87 samples were succesfully interviewed through telephone interviews. The instruments of this study was a questionnaire. Quantitative data was analysed using crosstab and percentages. While the qualitative data was analysed by categories. The results showed: (1) the graduates of the Fashion Design, the Hospitality, and the Make-up and Beauty Therapy Programmes who understand the job application process were 85%, 78%, and 86% respectively (b) the graduates of Fashion Design, Hospitality, and Make-up and Beauty Therapy Programmes with the less than 6 months waiting period before the first employement were 85%, 100%, 80%  respectively (c) The graduates of Fashion Design, Hospitality, and Make-up and Beauty Therapy Programmes who get job vacancies from advertisements and direct application to the company were 15% and 85%, 43% and 57%, 80% and 20% respectively. d. the graduates of Fashion Design, Hospitality, and Make-up and Beauty Therapy Programmes who are employed in the fields related to their study were 61.5% 71%, 60% respectively (2) The graduates’ competencies compared to the market needs were as follows: (a) Competencies required were integrity, mastery of science, English, information technology, communication, teamwork, self-development, mastery of skills, special expertise, leadership, and organizational management.  (b) 98% of the graduates have excellent performance in terms of integrity, expertise, science, English, information technology, communication, teamwork, and self-development.